BUSINESS STRATEGY ARCHITECTURE AT ESQ TOURS - Bramanto Wibisono; Yudha Heryawan Asnawi; Asep Taryana (Asian Journal of Social and Humanities, 2026)
The rapid growth of the Umrah and Hajj industry in Indonesia and globally presents both significant opportunities and competitive challenges for specialized travel organizers. This study examines the business strategy architecture at ESQ Tours (PT Fajrul Ikhsan Wisata), one of Indonesia's leading dedicated Umrah and Hajj travel agencies, established since 2005. The research aims to develop a comprehensive business strategy architecture aligned with the company's vision as a preferred and trusted halal tour operator in Southeast Asia. A qualitative descriptive approach was employed using a case study model, with data collected through direct observation, in-depth interviews, questionnaires, company annual reports, and literature reviews. Data analysis incorporated a multi-layered strategic framework, including foresight analysis, PESTLE, Porter's Five Forces, VRIO, Activity-Based Management (ABM), SWOT, TOWS Matrix, and the A'WOT (AHP-SWOT) method to prioritize strategic choices. The External Factor Evaluation (EFE) matrix yielded a score of 2.860 and the Internal Factor Evaluation (IFE) matrix scored 2.790, placing ESQ Tours in Quadrant V of the IE Matrix, recommending a "Hold and Maintain" strategy through market penetration and product development. Key findings reveal that ESQ Tours' primary competitive advantages lie in its unique ESQ 165-based meaning methodology and strong brand reputation, while its most critical weakness is the underutilization of the pilgrim waiting-period ecosystem. Three priority strategies were formulated: spiritual experience-based differentiation, strengthening unique value propositions, and service quality standardization. The resulting business strategy architecture for 2026–2030 is built upon two pillars—offensive differentiation and internal modernization—with a transformative shift from a transactional to a relational and sustainable business model through activation of the Hajj waiting congregation ecosystem.